Pemenuhan Kebutuhan Mobilisasi Dini terhadap Penyembuhan Luka pada Pasien Sectio Caesarea di Rumah Sakit Tk. II Putri Hijau Medan - Evamona Sinuraya; Muhammad Winanda (PubHealth Jurnal Kesehatan Masyarakat, 2022)
Section Caesarea is a childbirth done by incision through abdomen wall. Indication of doing Section Caesarea are repeated Section Caesarea, on the request of the women, old primigravida, dystocia, fetus emergency, early rupture of membranes, previa placenta, and old partum. Early mobilization is an enabling factor in accelerating post-surgery recovery and preventing complication since the wound needs good blood circulation to the growth or improvement of cells. The research used descriptive method with nursing process approach in 2 Section Caesarea patients with early mobilization technique at Putri Hijau Level II Hospital, Medan. In the post-nursing intervention, using early mobilization, the patients Physical mobility could gradually be fulfilled. The con conclusion was the patients were willing to do early mobilization step by step so that the recovery could be achieved early. It is recommended that nursing increase their guidance to Section Caesarea patients in doing early mobilization step by step.